Social housing and urban renewal : a cross-national perspective - Watt, Paul; Smets, Peer (Emerald Publishing, 2017)
This book offers a cross-national perspective on contemporary urban renewal in relation to social rental housing. Recent renewal has involved demolishing many social housing estates and replacing them with mixed-tenure housing developments in which deconcentration of poverty and social mixing of poor tenants and wealthy homeowners are major goals.
Keywords: Public housing.; Urban renewal.; elektronické knihy; electronic books